The influence of microbial mutualistic interactions and biofilm formation on the performance microbial fuel cell - Islam, Mohammed Amirul (2018)
Microbial fuel cell (MFC) is an electrochemical device that directly converts chemical energy of wastes into electricity by the metabolic activity of microorganisms. The performance of MFC can be affected by several key parameters such as reactor configurations, electrode materials, electrode surface area, membrane, biofilm thickness, and inoculum. Among them, the microbial community composition and the anode biofilm severely influence the performance of MFC. To prepare effective inoculum, the choice of microorganisms should be based on their ability to utilize complex substrates and the electrogenic properties. In this context, the performance of targeted pure cultures (Klebsiella variicola, Klbesiella pneumonia, Bacillus cereus and Pseudomonas aeruginosa) were investigated in palm oil mill effluent (POME) driven MFC. The targeted bacteria were isolated and characterized using BIOLOG gene III, polymerase chain reaction (PCR) and sequencing analysis. The effect of time-course biofilm formation by the microorganisms on MFC performance was visualized using field emission electron microscopy (FESEM) and characterized by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) analysis. The accumulation of dead cells in the multilayer biofilm at the vicinity of the electrode surface over time within the anode biofilm was found to be particularly detrimental to current generation that increased the charge transfer and diffusion resistances confirmed by EIS. Flow induced shear stresses and ultrasound-assisted methods were employed to revitalize the biofilm by removing inert biomass for the maintenance of stable power in MFCs. The hydrodynamic shear stress of 9.34 mPa and the 30 min of ultrasound treatment (20 kHz) successfully reduced the thickness of biofilm thus it revitalized within a short time by increasing the cell growth rate of the biofilm. The mechanism of electron transfer was elucidated using CV analysis. Furthermore, the co-culture and mixed cultures inoculum was developed using targeted bacteria (Klebsiella variicola and Bacillus cereus, Klebsiella variicola and Pseudomonas aeruginosa, Bacillus cereus and Pseudomonas aeruginosa, Klebsiella variicola and Bacillus cereus and Pseudomonas aeruginosa). The highest power density of 14.78 W/m3 was achieved by Pseudomonas aeruginosa and Klebsiella variicola co-culture inoculum due to their synergistic relationships which are inter-linked via fermentation-based metabolite. Besides, the interaction of Klebsiella variicola and Bacillus cereus positively influenced the power generation and the coculture inoculum obtained maximum power density of 11.78 W/m3 whereas the antagonistic relationship was witnessed for Bacillus cereus and Pseudomonas aeruginosa. Apart from that the performance of Klebsiella variicola and Pseudomonas aeruginosa co-culture was optimized with respect of operational parameters (substrate concentration, different ratio of microorganisms, pH and time) by using response surface methodology (RSM). The inoculum composition (different ratios of Klebsiella variicola and Pseudomonas aeruginosa) played a crucial role in simultaneous power generation and chemical oxygen demand (COD) removal from POME. These findings demonstrate that the synergistic interaction of microorganisms in inoculum and their subsequent effective biofilm formation are crucial to achieve the enhanced power generation in MFCs that can potentially be implemented for POME treatment.